Water quality management and pollution control a global overview - Horak, Bruce (Callisto Reference, 2015)
Water is a prerequisite for any form of life. The level of surface water quality protection is uneven around the world due to the relative efficiency of ecological instruction and the scale to which science influences the regulatory procedure. In the US, the Total Maximum Daily Load (TMDL) has been a triumphant policy for water quality treatment process. The TMDL offers a balanced structure for estimating the assimilative capability of the receiving water body for certain contaminants, applying factors of security and incorporating suitable levels of water quality criteria violation - provided the local stakeholders have a say in the decision making process. This book is a compilation of all such researches which will help our readers in understanding the topic better.